Application of Big Data and Internet of Things Technology in the Management of Financial Operating Income of Electric Power Enterprises. (19th September 2022) - Su, Huiling
Abstract : Aim. In order to effectively integrate and rationally allocate the complex information flow of people, finance, and materials in the daily operation of the enterprise and improve the daily operation efficiency and management effect of the enterprise, the author proposes a method for the application of big data and Internet of Things technology in the management of financial operating income of electric power enterprises. The method specifically includes an overview of the relevant theories of financial management based on ERP and an analysis of the needs of a power company's financial management system based on ERP so as to construct an evaluation index system for the financial management system. The experimental results show that the return on assets of the experimental enterprises has increased from 27.48% in 2015 to 55.18% in 2019, an increase of 27.7%, and the profitability has been continuously enhanced. In 2019, the company achieved a net profit of 392 million yuan, an increase of about 4 times compared with the previous 77 million yuan in 2015. Conclusion . The application can further optimize the allocation of various resources of the enterprise and ensure the effective implementation of the long-term strategy and management goals of the enterprise on the basis of realizing the management needs of the enterprise.